Living experiences of people with advance cancer with low socioeconomic status: A systematic review of qualitative evidence. (April 2023) - Meng, Xianmei; An, Zifen; Xu, Yuying; Du, Jiayi; Tan, Lanhui; Yu, Huidan; Yu, Liping
Background: The number of patients with advanced cancer is rapidly increasing, and the subgroup of this population with low socioeconomic status has suffered more disease burden than others. However, there is no recent qualitative synthesis of primary research studies into advanced cancer patients with low socioeconomic status. Objective: To synthesise qualitative research findings into advanced cancer patients' experiences with low socioeconomic status, and then to help provide targeted and effective strategies to improve their quality of life. Design: A systematic review and meta-synthesis of qualitative evidence (PROSPERO: CRD42021250423). Data sources: PubMed, Web of Science Core Collection (ISI Web of Science), Cochrane Library, Embase, OVID LWW, CINAHL Complete (EBSCO), PsycINFO (EBSCO) and MEDLINE (ISI Web of Science), China National Knowledge Infrastructure (CNKI), WangFang, and Vip databases were systematically searched from their original dates to July 2022. Qualitative data were appraised using the Joanna Briggs Institute (JBI) qualitative assessment. Findings: The findings were synthesised into the following three analytical themes: (1) multi-dimensional disease distresses; (2) barriers in coping with disease distresses; and (3) strategies for dealing with disease distresses. Conclusions: Patients with advanced cancer with low socioeconomic status experienced complicated and interactional distresses, unique life barriers, and a wide range of adaptation strategies. These findings will provide a comprehensive perspective to promote individual-centred health care systems and services to help these vulnerable people deal with the challenges of disease and improve their quality of life.